2013
DOI: 10.1111/infa.12043
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Some Toddlers Help A Stranger? Origins of Individual Differences in Prosocial Behavior

Abstract: This study investigated the influence of emotion on toddlers' prosocial behavior in instrumental helping tasks with an unfamiliar adult. The goals were to examine whether early prosocial behavior was affected by (1) the adult's expressions of sadness (in contrast to a neutral expression) as a cue of need and (2) toddlers' emotion understanding. Thirty-five 18-to 20-month-olds participated in eight trials in which an experimenter either indicated need for assistance (experimental condition) or did not (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 10 publications
7
28
0
1
Order By: Relevance
“…The current findings are in line with those from Vaish et al (2009) and Newton et al (2014), who demonstrated that infants are willing to subsequently help individuals who displayed neutral facial expressions following a negative scene. Interestingly, our study extends these findings by showing that infants display less concern for “neutral” than sad individuals after a negative event, but are equally willing to help and imitate them and be guided by their emotional expressions, perhaps giving them “the benefit of the doubt”.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The current findings are in line with those from Vaish et al (2009) and Newton et al (2014), who demonstrated that infants are willing to subsequently help individuals who displayed neutral facial expressions following a negative scene. Interestingly, our study extends these findings by showing that infants display less concern for “neutral” than sad individuals after a negative event, but are equally willing to help and imitate them and be guided by their emotional expressions, perhaps giving them “the benefit of the doubt”.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, if infants are sensitive to the valence of emotional expressions, it was hypothesized that they would show less concerned reactions towards a neutral individual following a negative event than towards a sad individual. In line with previous findings (Chiarella & Poulin-Dubois, 2014; Newton et al, 2014), no differences were expected between the sad and neutral group on the imitation task or in the instrumental helping task. However, if infants detected the neutral individual as “unreliable”, then infants in the Neutral group would likely show less empathic helping and emotional referencing than those in the Sad group.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Bununla birlikte, yapılan araştırmalar yardım davranışlarındaki cinsiyet farklılıkları açısından tutarsız sonuçlar bildirdiği ve çalışmalar daha çok batı ülkelerinde yapıldığı için (Newton, Goodman ve Thompson, 2014;Svetlova ve arkadaşları, 2010;Warneken ve Tomasello, 2007) bu araştırmada çocukların farklı koşullardaki araçsal yardım etme davranışlarında cinsiyet farklılıklarının görülüp görülmediği de incelenecektir.…”
unclassified